Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0896-6273(00)00097-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantal Release of Serotonin

Abstract: We have studied the origin of quantal variability for small synaptic vesicles (SSVs) and large dense-cored vesicles (LDCVs). As a model, we used serotonergic Retzius neurons of leech that allow for combined amperometrical and morphological analyses of quantal transmitter release. We find that the transmitter amount released by a SSV varies proportionally to the volume of the vesicle, suggesting that serotonin is stored at a constant intravesicular concentration and is completely discharged during exocytosis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
202
4
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(228 citation statements)
references
References 79 publications
18
202
4
4
Order By: Relevance
“…Although it is possible that a fraction of the neurotransmitter content remained inside the vesicle, the strong correlation between vesicle size and quantal size suggests that the vesicle neurotransmitter content was completely emptied under the stimulation conditions used in this study. These findings are similar to previous studies performed in different cell types that have reported that vesicle size has a strong influence on quantal size (33,(37)(38)(39). Our studies are consistent with AP-3 participating in neurosecretory vesicle formation and secretion.…”
Section: Vesicle Size Is Altered In a Manner That Mirrors Quantal Sizsupporting
confidence: 93%
“…Although it is possible that a fraction of the neurotransmitter content remained inside the vesicle, the strong correlation between vesicle size and quantal size suggests that the vesicle neurotransmitter content was completely emptied under the stimulation conditions used in this study. These findings are similar to previous studies performed in different cell types that have reported that vesicle size has a strong influence on quantal size (33,(37)(38)(39). Our studies are consistent with AP-3 participating in neurosecretory vesicle formation and secretion.…”
Section: Vesicle Size Is Altered In a Manner That Mirrors Quantal Sizsupporting
confidence: 93%
“…The set point of synaptic vesicle glutamate and GABA storage might therefore be controlled by the number of functional transporters and the cytoplasmic transmitter concentration (Wilson et al, 2005) similarly to that described for the vesicular acetylcholine transporter after heterologous gene expression Erickson, 1996, 1997), supporting a steady-state equilibrium model of vesicle transmitter packet size (Williams, 1997). The rate of vesicular transmitter uptake Song et al, 1997) and the size of synaptic vesicles have also been considered to be determinants of quantal size (Bruns et al, 2000;Colliver et al, 2000;Pothos et al, 2000;Sulzer and Pothos, 2000;Karunanithi et al, 2002;Van der Kloot et al, 2002;Gong et al, 2003). VGLUT1 overexpression at excitatory synapses of Drosophila results in an increase in vesicle volume, which is accompanied by an increase in quantal size of glutamate measured postsynaptically (Daniels et al, 2004).…”
Section: Scaling Of Vesicular Glutamate and Gaba Transporter Expressionmentioning
confidence: 77%
“…Unlike mIPSCs (Llano et al, 2000), large mEPSCs recorded from CA3 pyramidal cells are insensitive to manipulations of intracellular and extracellular Ca 2ϩ (Henze et al, 2002). Alternatively, the skew in miniature amplitude distribution can result from variations in vesicular glutamate content (Bruns et al, 2000;Karunanithi et al, 2002). If this is the case, cube root transformation of amplitude or charge measurements should yield a distribution pattern similar to the distribution pattern of vesicle radius measurements.…”
Section: Resultsmentioning
confidence: 99%